1988
DOI: 10.1016/0014-5793(88)80730-0
|View full text |Cite
|
Sign up to set email alerts
|

NADPH‐dependent metabolism of the ribulose bisphosphate carboxylase/oxygenase inhibitor 2‐carboxyarabinitol 1‐phosphate by a chloroplast protein

Abstract: Metabolism of 2-carboxyarabinitol l-phosphate (CA l-P), an endogenous inhibitor of ribulose. bisphosphate carboxylase/ oxygenase, occurs in the light. A soluble protein fraction which metabolized CA 1-P in the presence of NADPH was isolated from tobacco chloroplasts. A similar fraction from spinach exhibited much lower activity. The activity in tobacco extracts was stable overnight at 4°C but its maintenance during storage required dithiothreitol. The tobacco protein responsible for CA 1-P metabolism was parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…The total k,.t of Rubisco in S. oleracea was initially high (approximately 20 s') at the low PFD values of the early morning (Fig. 3C).…”
Section: Metabolite and Rubisco Analysesmentioning
confidence: 93%
See 2 more Smart Citations
“…The total k,.t of Rubisco in S. oleracea was initially high (approximately 20 s') at the low PFD values of the early morning (Fig. 3C).…”
Section: Metabolite and Rubisco Analysesmentioning
confidence: 93%
“…As the PFD increased in the morning, in contrast to the other species the total k., of S. oleracea Rubisco decreased, reaching a minimum of 13 s-' at approximately 100 Mmol quanta m-2 s-'. As PFD increased further the total k.t then increased, attaining a maximum of approximately 20 s-' at 400 Mmol quanta m-2 s-'. The Rubisco total k.t of S. oleracea then remained relatively constant until the middle of the afternoon.…”
Section: Metabolite and Rubisco Analysesmentioning
confidence: 98%
See 1 more Smart Citation
“…The two effectors compete to produce a net catalytic rate. At a constant concentration of CA I -P, in the absence of Pi, 10 mm FBP stimulates During initial experiments on the isolation of CA 1-Pase, it was noted that maintenance of enzyme activity required storage in the presence of DTT (4,19). For this reason, most subsequent experiments with CA 1-Pase have also routinely included 4 mm DTT in the assay medium (7,20).…”
Section: Effect Of Fbp and Pi On Ca 1-pase Activitymentioning
confidence: 99%
“…Archie agreed and Simon contacted Joe Berry, who kindly provided a sample for the experiments. Previous work on CA1P had shown that its release from Rubisco was very slow (Berry et al 1987) and that CA1Pase could only hydrolyze CA1P once it was released (Salvucci et al 1988). Robinson and Portis showed that activase was indeed active towards CA1P, facilitating its release from Rubisco to make it available for metabolism by CA1P phosphatase (Robinson and Portis 1988).…”
Section: Ca1p -A Red Herring?mentioning
confidence: 99%